2022
DOI: 10.1186/s40104-022-00769-1
|View full text |Cite
|
Sign up to set email alerts
|

Advances on genetic and genomic studies of ALV resistance

Abstract: Avian leukosis (AL) is a general term for a variety of neoplastic diseases in avian caused by avian leukosis virus (ALV). No vaccine or drug is currently available for the disease. Therefore, the disease can result in severe economic losses in poultry flocks. Increasing the resistance of poultry to ALV may be one effective strategy. In this review, we provide an overview of the roles of genes associated with ALV infection in the poultry genome, including endogenous retroviruses, virus receptors, interferon-sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 175 publications
0
5
0
Order By: Relevance
“…ALV is an avian oncogenic retrovirus that can cause growth retardation, reduced egg production, and immunosuppression [ 12 ]. Subclinical pathological and various neoplastic diseases have caused huge economic losses to the poultry industry [ 10 ]. Like all retrovirus diseases, AL is difficult to prevent and control with vaccines and drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALV is an avian oncogenic retrovirus that can cause growth retardation, reduced egg production, and immunosuppression [ 12 ]. Subclinical pathological and various neoplastic diseases have caused huge economic losses to the poultry industry [ 10 ]. Like all retrovirus diseases, AL is difficult to prevent and control with vaccines and drugs.…”
Section: Discussionmentioning
confidence: 99%
“…These methods can efficiently differentiate between two or three subtypes of ALV but cannot simultaneously distinguish ALV-A/B/J/K subtypes. In addition, ALV can generate genetic variability and evolve rapidly through RNA error-prone polymerase and frequent recombination events that lead to the emergence of many new mutant and recombinant strains [ 10 , 11 ]. Hence, it is necessary to improve the existing molecular detection techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research about the distribution of endogenous retroviruses in the mammals and avian genome revealed that most of these fragments are enriched outside transcription units in reverse orientation relative to the host [43][44][45]. Considering the research of endogenous retrovirus biology, integration outside transcription units may be primarily benign and was preserved during evolution [11,46].…”
Section: Discussionmentioning
confidence: 99%
“…Avian leukosis virus ( ALV ) is a retrovirus that can induce various malignant tumors such as myeloma, hemangioma, and connective tissue tumor, causing severe immune damage to the host ( Rubin, 2011 ; Guo et al, 2014 ; Lipsick, 2021 ). ALV is divided into 11 subgroups based on the specificity of the glycoprotein gp85 on the viral envelope ( Mo et al, 2022 ), the cross reaction patterns between virus and host factors ( Cui et al, 2014 ). Seven subgroups including A, B, C, D, E, J, and K originate from chickens, with A, B, C, D, J, and K being exogenous viruses ( Wang et al, 2012 ) and E being endogenous viruses ( Su et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%